Advanced Study on Yield Curve as a Leading Indicator in Predicting Economic Slowdowns: An Evidence from India - Khandwala, Hemal (Insights into Economics and Management Vol. 8, 2021)
There exists literature that explores the linkages between yield curve, economic activity and monetary policy. Although empirical work has been done to show the significance of the slope of yield curve in predicting economic slowdowns, it has predominantly been for the developed markets of the US, Europe and so on. This paper explores the predictive power of the slope of yield curve in forecasting economic slowdowns in India through the use of wavelet based filtering. We develop a new approach using duration models to enable the construction of real time forecasting of recession probabilities. Our study suggests strong empirical evidence of the impact of the yield curve in predicting economic slowdowns in India. Monetary policy directly affects the yield curve which acts as a leading indicator in predicting the macro economic activity over longer horizons of time with strongest impact observed over periods of 8 to 16 quarters (2 to 4 years).